Hubungan kemampuan literasi sains terhadap keterampilan berpikir kreatif siswa kelas IV di SDN Sambirejo Surakarta tahun ajaran 2023/2024 - Febrianti, Anggi; Jumanto, Jumanto; Handayani, Sri (Jurnal Pendidikan Dasar, 2024)
Abstract. This research aims to analyze the relationship between scientific literacy abilities and critical thinking skills of grade 4 students at SDN Sambirejo Surakarta in the 2023/2024 academic year. This research is a correlational quantitative research. The data source for this research is grade 4 students at SDN Sambirejo. The sampling technique was carried out using a saturated sample, so that the sample for this research was all 28 class IV students at SDN Sambirejo. Data collection was carried out using cognitive and observation test questions. Instrument testing uses validity and reliability tests with SPSS 26.0. Data analysis consists of prerequisite analysis tests and hypothesis testing. The analysis prerequisite tests consist of normality tests and linearity tests. Hypothesis testing is carried out using simple correlation analysis. The results of this research show that scientific literacy abilities have a positive and significant relationship with students' creative thinking skills with a significance value based on the Spearman Rank correlation test < 5%, namely 0.003 and the correlation coefficient for scientific literacy abilities with creative thinking skills has a value of 0.548, which means it is in strong category because it is in the value range of 0.51-0.75.Kata kunci: Connection, Scientific Literacy, Creative Thinking